Optimisation of ultrasonic- and enzyme-assisted methods for production of fructooligosaccharides-rich yacon [Smallanthus sonchifolius (Poepp.) H. Rob.] syrup - Chong, Florence Huey Lin (2019)
Yacon [Smallanthus sonchifolius (Poepp.) H. Rob.] is a highly nutritious tuberous root. It is often extracted conventionally and undergoes multiple harsh processes for long hours causing the deterioration of important compounds such as oligosaccharides and phenolic compounds. Consequently, this research was performed to optimise ultrasonicassisted and enzyme-assisted methods for the production of fructooligosaccharides (FOS)-rich syrup from yacon. Optimisation was carried out on single response (highest yield (HY), highest antioxidant activity (HA) and highest total soluble solids (HTSS)) and multiple responses for both extraction methods. The saccharide compounds in all the optimised syrups were identified and quantified with LC-Q-TOF-MS and HPLC-RI, respectively. Enzyme-assisted extraction produced the highest yield (HY) syrup using parameters such as low solute to solvent ratio (1:80), high enzyme percentage (1.00%), low temperature (30 °C) and long extraction time (4.0 h). The highest total soluble solids (HTSS) sample using enzyme-assisted extraction was attained with 4.0 h extraction time using 1.00% enzyme percentage and solute to solvent ratio of 1:20 at 30 °C. The optimisation analysis of the highest antioxidant activity (HA) revealed that ultrasonicassisted extraction resulted in syrup with lower IC50 than the enzyme-assisted extraction. The highest antioxidant activity (HA) condition from ultrasonic-assisted extraction was 1:80 solute to solvent ratio and 70% amplitude for 30 min in a continuous mode. The most desirable extraction condition for the ultrasonic-assisted extraction of fructooligosaccharides-rich yacon syrup established in this study was 1:80 solute to solvent ratio, 5.0 min extraction time, 20% amplitude and 10 s pulsed interval. In contrast, the most desirable set of conditions for enzyme-assisted extraction was 1:20 solute to solvent ratio, 1.00% enzyme percentage, 30 °C temperature and 1.0 h extraction time. The physicochemical analysis results from the optimum condition samples revealed that enzyme-assisted extraction was a more effective extraction method. Nevertheless, the duration of the extraction processes was greatly reduced with ultrasonic-assisted extraction. Both the optimum condition syrups contained saccharides compounds such as 1-kestose (GF2), nystose (GF3), sucrose, fructose and glucose. In contrast, fructofuranosylnystose (GF4) was only identified in the optimum condition of enzyme-assisted extraction yacon syrup. Between the optimum conditions samples, higher FOS content was discovered in the optimum condition of enzyme-assisted extraction syrup at 31%. A greater amount of fructooligosaccharides allowed the optimum condition syrup from enzyme-assisted extraction to have a better capacity at lowering the glucose production rate and it was capable of exhibiting hypocholesterolemic effects. This study deduced that the optimum enzyme-assisted extraction condition is more efficient to extract higher quality of fructooligosaccharidesrich yacon syrup with greater amounts of fructooligosaccharides, antioxidant activity and total soluble solids than the optimum ultrasonic-assisted extraction condition, although it was more economical.